Can Individuals with Suboptimal Antibody Responses to Conventional Antiviral Vaccines Acquire Adequate Antibodies from SARS-CoV-2 mRNA Vaccination? - Wataru Ogura; Kouki Ohtsuka; Sachiko Matsuura; Takahiro Okuyama; Satsuki Matsushima; Satoko Yamasaki; Hiroyuki Miyagi; Kumiko Sekiguchi; Hiroaki Ohnishi; Takashi Watanabe (Viruses, 2022)
In Japan, healthcare workers (HCWs) are vaccinated against measles, rubella, chickenpox, mumps, and hepatitis B to prevent nosocomial infection; however, some do not produce sufficient antibodies (“suboptimal responders”). This study compared immune responses to a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 mRNA) vaccine among HCWs with normal and suboptimal responses to conventional vaccines. In this prospective cohort study, 50 HCWs received two doses of BNT162b2 mRNA vaccine 3 weeks apart. SARS-CoV-2 anti-spike antibodies were measured 11 times, starting before the first vaccination and ending 5 months after the second vaccination. Antibody titers of four suboptimal and 46 normal responders were compared. SARS-CoV-2 neutralizing antibody activity was measured twice in suboptimal responders, 1 week/1 month and 5 months after the second vaccination. The SARS-CoV-2 anti-spike antibody was detectable in the samples from suboptimal and normal responders at each timepoint after vaccination. Suboptimal responders exhibited SARS-CoV-2 neutralizing antibody activity 1 week/1 month as well as 5 months after the second vaccination; however, activity was slightly reduced at 5 months. Our findings show that suboptimal responders do acquire adequate SARS-CoV-2 anti-spike and SARS-CoV-2 neutralizing antibodies from vaccination to prevent SARS-CoV-2. SARS-CoV-2 mRNA vaccines should thus be recommended for both normal and suboptimal responders to conventional vaccines.